2006
DOI: 10.5642/aliso.20062201.24
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Genome Size, and Chromosome Evolution of Asparagales

Abstract: Asparagales are a diverse monophyletic order that has numerous species (ca. 50% of monocots) including important crop plants such as Allium, Asparagus, and Vanilla, and a host of ornamentals such as irises, hyacinths, and orchids. Historically, Asparagales have been of interest partly because of their fascinating chromosomal evolution. We examine the evolutionary dynamics of Asparagales genomes in an updated phylogenetic framework that combines analyses of seven gene regions (atpl, atpB, matK, ndhF, rbcL, trn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
81
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 90 publications
24
81
3
2
Order By: Relevance
“…A series of studies during the past decade resolved molecular phylogenetic relationships among a broad sample of representatives of Asparagales (e.g. Fay et al, 2000;Bogler et al, 2006;Givnish et al, 2006;Pires et al, 2006). All these studies are very much congruent with each other concerning topology and strong support for several terminal clades recognized as families as well as some internal relationships.…”
Section: Bradleya 28/2010supporting
confidence: 56%
See 3 more Smart Citations
“…A series of studies during the past decade resolved molecular phylogenetic relationships among a broad sample of representatives of Asparagales (e.g. Fay et al, 2000;Bogler et al, 2006;Givnish et al, 2006;Pires et al, 2006). All these studies are very much congruent with each other concerning topology and strong support for several terminal clades recognized as families as well as some internal relationships.…”
Section: Bradleya 28/2010supporting
confidence: 56%
“…In contrast, Aloe and relatives are so firmly nested in the clade recognized as Asphodelaceae (e.g. Pires et al, 2006) that it is not feasible to recognize them as a separate family Aloaceae. Our suggestion for the classification of the diversity of succulent Asparagales families is congruent with the topologies published from molecular phylogenetic analyses and published phylogenetic classification systems (for references see above).…”
Section: Bradleya 28/2010mentioning
confidence: 99%
See 2 more Smart Citations
“…Their analyses showed that a subset of hypotheses are recovered rarely when used as model trees, while others may be recovered frequently when they are not used to simulate data (i.e., high potential for type I and II errors). We therefore performed two basic sets of analyses with Aphyllanthes L. included or excluded from consideration (for more on this problematic taxon, see Fay et al [2000]; Chase et al 2006;Pires et al 2006); Ceratophyllum and Chloranthaceae were included in both cases.…”
Section: Alignment and Phylogenetic Analysismentioning
confidence: 99%